The Verbal Analysis in the Movie Posters of the GDH559 Movie from the Instagram - Lekphet, Lapadrada; Srirasa, Chuthamat (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 2 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The verbal analysis of the movie posters of the GDH559 movie from the Instagram application is intended to study the verbal language in the posters of the GDH559 movie from the Instagram application 8 stories totaling 262 images. The verbal language found in the movie posters of the GDH559 movie record is divided into 2 types; 1) Advertising headline and 2) Detailed description text. The advertising headline is divided into 2 types. They are Main headline and Secondary headline. The most descriptive sentence headlines are found in the main headline, while the secondary headline section is found in every movie poster of the GDH559 movie. In addition, the text of the description is also found in every movie poster of the GDH559 movie as well. Movie posters of the GDH559 movie can cover the contents within 1 page and can also attract viewers to decide to buy movie tickets to watch movies.